2021
DOI: 10.12659/msm.930232
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implant Outcomes in Prelingually Deafened Adults with and without Sound Deprivation: Are There Differences in Quality of Life?

Abstract: Background Indications for cochlear implantation (CI) are constantly being updated, and with them, the audiometric results achieved by patients. Patient satisfaction should always be considered, even in patients with lower audiological results. The aim of the present study was to compare quality of life (QoL), self-perceived hearing benefit, and audiometric results between prelingually and postlingually deafened patients, with and without sound deprivation, after CI. Material/Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Therefore, we concluded that vowel recognition instead of monosyllable words hase potential to predict social-emotional functions in Mandarin-speaking adult CI recipients. However, Canale et al (26) reported that disyllabic words were significantly negatively correlated with the World Health Organization Quality of Life (WHOQOL) questionnaire scores, in contrast to our results. We speculate that the WHOQOL questionnaire is a generic QoL scale; therefore, it may have poor sensitivity for CI users.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, we concluded that vowel recognition instead of monosyllable words hase potential to predict social-emotional functions in Mandarin-speaking adult CI recipients. However, Canale et al (26) reported that disyllabic words were significantly negatively correlated with the World Health Organization Quality of Life (WHOQOL) questionnaire scores, in contrast to our results. We speculate that the WHOQOL questionnaire is a generic QoL scale; therefore, it may have poor sensitivity for CI users.…”
Section: Discussioncontrasting
confidence: 99%
“…While some authors only describe audiological performances worsening in noisy conditions [44], others describe a general worsening of vocal recognition as age increases [47]. Nevertheless, cochlear implantation has no age limitations, due to the significant improvement in life quality reported by implanted elderly patients [48][49][50].…”
Section: Clinical Characteristics and Predictorsmentioning
confidence: 99%
“…Jednakże trudno jest ocenić skalę tego zjawiska. [20] oraz czy jest to głuchota/ ubytek słuchu w stopniu głębokim czy głuchota częściowa [24].…”
Section: Wprowadzenieunclassified